2022
DOI: 10.2196/27402
|View full text |Cite
|
Sign up to set email alerts
|

A Web-Based App for Emotional Management During the COVID-19 Pandemic: Platform Development and Retrospective Analysis of its Use Throughout Two Waves of the Outbreak in Spain

Abstract: Background Quarantines and nationwide lockdowns implemented for containing the spread of the COVID-19 pandemic may lead to distress and increase the frequency of anxiety and depression symptoms among the general population. During the nationwide lockdown of the first wave of the COVID-19 outbreak in Spain, we developed and launched a web-based app to promote emotional self-care in the general population and facilitate contact with health care professionals. Objecti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Finally, Yoshioka et al, observed that the decreasing trend in suicides experienced in Japan during the 2016-2019 period was reverted in the overall 2020-2021 period, although a delay of several months in the rough observed cases was reported [15]. Interestingly, the strict lockdown period, an important stressor associated with an increased number of anxiety episodes and psychiatric consultations in our area [7,21], was followed by a drop in suicidal behavior events in our analysis. This phenomenon, observed also in a city-based study in our area [22], is in line with the decreasing demand for the suicide prevention helpline observed in a nation-wide analysis in the Netherlands right after the general lockdown [12]; of note, a partial lockdown dictated in that country eight months after was followed by a demand peak in the service.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Finally, Yoshioka et al, observed that the decreasing trend in suicides experienced in Japan during the 2016-2019 period was reverted in the overall 2020-2021 period, although a delay of several months in the rough observed cases was reported [15]. Interestingly, the strict lockdown period, an important stressor associated with an increased number of anxiety episodes and psychiatric consultations in our area [7,21], was followed by a drop in suicidal behavior events in our analysis. This phenomenon, observed also in a city-based study in our area [22], is in line with the decreasing demand for the suicide prevention helpline observed in a nation-wide analysis in the Netherlands right after the general lockdown [12]; of note, a partial lockdown dictated in that country eight months after was followed by a demand peak in the service.…”
Section: Discussionmentioning
confidence: 98%
“…Aside from the stressors directly derived from social distancing, other factors such as uncertainty associated with the pandemic scenario, impossibility of accompanying loved ones during their hospital stay or end-of-life stage, or financial crises (including unemployment) experienced in many countries have contributed to psychological overwhelming in many cases [6]. Likewise, the persistence of the health crisis, with alternating periods of normal live and social restrictions due to successive waves of the COVID-19 has caused learned helplessness behaviors, increasing the risk of depressive disorders [7]. Irrespective of the cause of mental health decline, various authors have reported increasing use of mental health services during the pandemic [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, most of the participants in both groups identified the rural area as their area of residence. The acceptability and effectiveness of eHealth tools to complement communication and supportive processes throughout the cancer care journey are increasingly recognized [ 33 ], particularly to bridge geographical disparities [ 41 ]. Yet, evidence suggests the need for embedding such innovative tools as part of a clinical workflow, ideally grounded on person-centered care principles so that they are put in use to favor the therapeutical relationship and shared decision-making at distance [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…This delay was in line with our analysis, which revealed a lag time of almost 4 months after the declaration of the state of emergency and population lockdown. Interestingly, our analysis showed that the strict lockdown period, an important stressor associated with an increased number of anxiety episodes and psychiatric consultations in our area [ 7 , 21 ], was followed by a drop in suicidal behavior events. This phenomenon was also observed in a city-based study in our area [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Aside from the stressors directly derived from social distancing, other factors, such as the uncertainty associated with the pandemic scenario, the impossibility of accompanying loved ones during hospital stays or end-of-life stages, or the financial crises (including unemployment) experienced in many countries, have contributed to psychological overwhelming in many cases [ 6 ]. Likewise, successive waves of COVID-19 translated into periods of the intensification and relaxing of social restrictions, according to infectious transmission rates; such intermittent distortions of social interaction have caused learned helplessness behaviors, increasing the risk of depressive disorders [ 7 ]. Irrespective of the cause of declining mental health, various authors have reported the increasing use of mental health services during the pandemic [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%